The Relationship between Perceived Benefits and Perceived Ease of Use with Actual Use of the E-Link Health Center Management Information System at the Slawe Health Center, Trenggalek Regency: Hubungan Persepsi Manfaat Dan Persepsi Kemudahan Penggunaan Dengan Penggunaan Aktual Sistem Informasi Manajemen Puskesmas E-Link Di Puskesmas Slawe Kabupaten Trenggalek - Hartini, Hartini; Mulyono, Sri; Sutrisnon, Trismianto Asmo (Procedia of Engineering and Life Science, 2025)
SIMPUS e-Link is a form of support for the Community Health Center Information System which is able to guarantee data and information that is fast, accurate, up-to-date, sustainable and accountable. The aim of the research is to analyze the relationship between perceived usefulness and perceived ease of use with the actual use of the Community Health Center Information System at the Slawe. Community Health Center, Trenggalek Regency. This research is a quantitative research using a cross sectional approach. The sample size for this study was 51 community health center staff users. The independent variable is perceived usefulness and convenience, while the dependent variable is actual use. The instrument of this research is a questionnaire whose validity and reliability have been tested. The research results showed that respondents had a good category of perceived benefits as much as 94.1%, perceived ease of use was in a good category (90.2%) and the actual usage variable was in a good category (72.5%). The results of statistical analysis show that the perceived usefulness variable is related to the actual use of SIMPUS with a value of p = 0.0001 (< 0.05), and a value of r = 0.84, which means there is a positive and strong relationship between perceived usefulness and actual use of SIMPUS e-Link. The variable perceived ease of use and actual use of SIMPUS has a significant relationship with a value of p = 0.0001, and a value of r = 0.78, which means there is a positive and strong relationship between perceived ease of use and actual use of SIMPUS e-Link. The conclusion of this research is Perceptions of the benefits of SIMPUS e-Link and ease of use of SIMPUS e-Link are related to actual use.